PENGEMBANGAN GAME EDUKATIF BERBASIS SMART APPS CREATOR DALAM MENINGKATKAN LITERASI KESEHATAN ANAK - Roby Naufal Arzaqi; Karunia Rahayu, Aisah (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
Early childhood health literacy is an important skill that supports the formation of healthy living habits from an early age. However, health literacy learning is often less attractive to children because it is delivered passively. This research aims to develop a prototype of an interactive educational Game specifically designed to improve early childhood health literacy. The research method used is Research and Development (R&D) with the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation (Branch, 2009). This study focuses on the Development stage, which includes a needs analysis through interviews with three early childhood education teachers, one pediatrician (as early childhood and health literacy expert), and one IT specialist (as game prototype development expert). The results of the study show that relevant health literacy themes include personal hygiene, healthy diet, and physical activity. The Game prototype "Clean and Healthy Adventure with Vivi and Vito" is designed with four interactive levels that use simple visual and narrative elements. Early validation by one IT expert showed the Game was exciting and suitable for early childhood with a few minor tweaks. The prototype is ready to be further tested to measure its effectiveness as an innovative and interactive and fun learning medium.